ELEMENT PARTITIONING DURING PRECIPITATION OF ARAGONITE FROM SEAWATER: A FRAMEWORK FOR UNDERSTANDING PALEOPROXIES - Gaetani G.A.; Cohen A.L. (My University, 2006)
This study presents the results from precipitation experiments carried out to investigate the partitioning of the alkaline earth cations Mg2+, Ca2+, Sr2+, and Ba2+ between abiogenic aragonite and seawater as a function of temperature. Experiments were carried out at 5 to 75 °C, using the protocol of Kinsman and Holland [Kinsman, D.J.J., Holland, H.D., 1969. The coprecipitation of cations with CaCO3 IV. The coprecipitation of Sr2+ with aragonite between 16 and 96 °C. Geochim. Cosmochim. Acta 33, 1-17.] The concentrations of Mg Sr and Ba were determined in the fluid from each experiment by inductively coupled plasma-mass spectrometry, and in individual aragonite grains by secondary ion mass spectrometry. The experimentally produced aragonite grains are enriched in trace components ("impurities") relative to the concentrations expected from crystal-fluid equilibrium, indicating that kinetic processes are controlling element distribution. Our data are not consistent with fractionations produced kinetically in a boundary layer adjacent to the growing crystal because Sr2+, a compatible element, is enriched rather than depleted in the aragonite. Element compatibilities, and the systematic change in partitioning with temperature, can be explained by the process of surface entrapment proposed by Watson and Liang [Watson, E.B., Liang, Y., 1995. A simple model for sector zoning in slowly grown crystals: implications for growth rate and lattice diffusion, with emphasis on accessory minerals in crustal rocks. Am. Mineral. 80, 1179-1187] and Watson [Watson, E.B., 1996. Surface enrichment and trace-element uptake during crystal growth. Geochim. Cosmochim. Acta 60, 5013-5020; Watson, E.B., 2004. A conceptual model for near-surface kinetic controls on the trace-element and stable isotope composition of abiogenic calcite crystals. Geochim. Cosmochim. Acta 68, 1473-1488]. This process is thought to operate in regimes where the competition between crystal growth rate and diffusivity in the near-surface region limits the extent to which the solid can achieve partitioning equilibrium with the fluid. A comparison of the skeletal composition of Diploria labyrinthiformis (brain coral) collected on Bermuda with results from precipitation calculations carried out using our experimentally determined partition coefficients indicate that the fluid from which coral skeleton precipitates has a Sr/Ca ratio comparable to that of seawater, but is depleted in Mg and Ba, and that there are seasonal fluctuations in the mass fraction of aragonite precipitated from the calcifying fluid ("precipitation efficiency"). The combined effects of surface entrapment during aragonite growth and seasonal fluctuations in "precipitation efficiency" likely forms the basis for the temperature information recorded in the aragonite skeletons of Scleractinian corals. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ARAGONITE; FLUID COMPOSITION; PARTITION COEFFICIENT; TRACE ELEMENT; ANTHOZOA; DIPLORIA LABYRINTHIFORMIS; SCLERACTINIA